PERAN JASA PERBANKAN DALAM MENGATASI KETERBATASAN PEMBIAYAAN DAN MENINGKATKAN LITERASI KEUANGAN UMKM DI INDONESIA - Herlambang, Herlambang (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
This study aims to analyze the role of banking services in supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on addressing financing barriers and improving financial literacy. The issues discussed include limited MSME access to financing and low financial literacy among business actors. The research employs a qualitative descriptive analysis method using secondary data from journals, reports, and official publications. The findings reveal that banking plays a vital role in overcoming financing challenges through flexible product offerings, the use of digital banking services, and participation in MSME development programs. Moreover, financial literacy improvement is achieved through training programs, technology-based outreach, and innovative educational approaches like gamification. These solutions not only enhance MSMEs' access to banking services but also strengthen their financial management capabilities. The study concludes that banks play a strategic role in fostering MSME growth through inclusive and educational approaches. Collaboration among banks, MSMEs, and regulators is expected to sustainably address financing and financial literacy challenges.